Woman Resistance toward Domestic Roles in “Little Women” Novel by Louisa May Alcott: Feminist Approach - Lavinia Rosemary; Tomi Arianto (LPPM Universitas Bumigora Mataram, 2023)
Women’s resistance toward domestic roles is viewed from the main characters in the novel “Little Women”. This research aimed to see and analyze women's resistance toward domestic roles in the novel “Little Women” by Louisa May Alcott using Tiffany K Wayne theory of triple roles and feminism approach. To find out what kind of roles of women shown by the main characters in the novel “Little Women” based on triple roles theory by Tiffany K Wayne.To find out how women's resistance toward domestic roles can be seen from the characters in the novel